PEMANFAATAN TEKNOLOGI TEXT-TO-SPEECH SEBAGAI MEDIA PEMBELAJARAN PADA LABORATORIUM BAHASA INGGRIS - Kukuh Yudhistiro (Jurnal Teknologi dan Manajemen Informatika, 2016)
English learning laboratory is a very important facility to support the effectiveness and efficiency of the learning process teaching English in schools or other institutions pedidikan. Presence technology speech synthesizer (synthesizer speech), which is also known by the term system Text-To-Speech (TTS), can perform the conversion of the text produced computer in the form of pronunciation (audio), where the pronunciation is generated adjustable speed, intonation ( prosody), and the audio output format to be stored in the form of an audio file. This makes saving and keefesienan in the use of tools and without the use of instructional media were quickly worn media such as CDs and devices. DOI: https://doi.org/10.26905/jtmi.v2i1.622